(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Nowadays, Organic semiconductors (OSCs) are receiving increasing attention these days because they have many attractive properties – including light weight, low-cost production, low- temperature processing, mechanical flexibility, and abundant availability. Earlier, ISFET ( The ion sensitive field effect transistor) was used as a sensing device. It is used in measuring ion concentrationin the solution. It is based on inorganic field effect transistors where an electrolyte solution and ion- sensitive membrane is embedded. It is a special type of MOSFET in which gate electrode was replaved by refrence electrode and ion-sensistive layer. There are various categories of ISFET such as PH-ISFET, CHEM-ISFET, BIO-ISEFT etc. As these devices have many advantages,they show good compatibilitywith the CMOS technology ,controlling procesveprecisely,operates at equilibrium conditions,capable of showing label free detection and easy to use, still these devices suffer from few innate deficiency.In case of long term use they are unrelible , unstable due to ionic damage and shouldhave low SNR. For sensing purpose, the main principle involves a variation in the surface capacity that occurs due to ionic interactions at the electrolye/gate oxide. ISFET main constraint lies in the the poor sensing margin within the Nernstian limit (59 mV per pH) at room temperature and this has gained much research attention over the past few decades.So,diffedrent devices have been tried till now to improve the sensing margin(>59 mV per pH) and hence this results in different device design with different configurations .We also proceeded our work with the same aim to improve the Nernestian limit using Organic Field Effect Transistor as device and hence tried different configurations to get thedesired results.In our work, we have developed a dual gate organic field effect transistor (DG-OFET) based pH sensor that will be able to detect the variations in the aqueous (electrolyte) medium.In this structure source sided underlap technique with dual gate sensing approach has been used.The simulationresults were extracted with the help of software package Silvaco TCAD-ATLAS.The simulated results display that the proposed DG-OFET shows significantly higher sensitivity for different dielectrics.